Pesantren Raudhatul Ulum Dalam Pengembangan Sumber Daya Manusia - candra kirana (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2020)
Abstract This study aims to determine the concept or program of human resource development at Raudhatul Ulum Islamic Boarding School. The method in this research emphasizes the type of research file, while this qualitative approach is carried out as a research procedure that produces descriptive data in the form of written or oral words from people and the behavior observed by the author through observation, interviews and documentation regarding the development of Human Resources at Raudhatul Ulum Islamic Boarding School through the concept or program of the Directorate of HRD (Human Resources Development) of Raudhatul Ulum Islamic Boarding School. From the research results it is known that the Raudhatul Ulum Islamic Boarding School through Asdir Division (Human Resources Development) has a concept or program that is arranged systematically and planned Making a schedule of ongoing coaching with the qualifications of participants of educators, non-educators, students. Furthermore, monitoring to the evaluation stage of the program being run. The implementation process of Raudhatul Ulum Islamic Boarding School in developing Human Resources went quite well, most of the activities carried out went as planned by the pesantren. Based on the changes in the behavior of the Raudhatul Ulum Islamic Boarding School human resources after participating in a number of coaching activities and the rules applied by the HRD (Human Resources Development) the better, most of them showed good commitment to the pesantren, were able to work with sincerity and complete, have insight about Islam after participating in several activities and coaching.